Promoting the archives of the Alliance: a case study of outreach at the NATO Archives*. Issue 2 (1st August 2021) - Nguyen, Nicholas
Abstract : Following the institutionalization of the Policy on the Public Disclosure of North Atlantic Treaty Organization (NATO) Information in 2008, the NATO Archives tasked itself to regularly exhibit publicly disclosed NATO documents, video, audio, photos, publications and artifacts to promote the increasing accessibility of its collection. The success of these exhibitions, which were all initially displayed at NATO Headquarters in Brussels, led not only to a boost in the visibility of the NATO Archives within the organization, but also resulted in their expansion as part of the promotional activities of the Alliance itself, leading up to its 70th anniversary celebrations in 2019. This paper presents an overview of the outreach activities of the NATO Archives, discussing its origins and evolution in an institutional context, highlighting its role in communicating the mission of the NATO Archives and, by extension, of NATO itself. While this case study illuminates a specific experience that is heavily determined by the political and security demands of its particular environment, the resulting narrative is intended to be broadly applicable and perhaps even inspirational for archivists who recognize similar challenges at their respective international organizations.